Translation Problems that are Facing Future Translators (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the challenges that future translators are likely to face, including limitations of machine translation, language evolution, cultural sensitivities, and specialized domains. The analysis is based on a review of existing literature and highlights the importance of human intervention in translation despite technological advancements. Suggestions for addressing these challenges include continuous professional development, cultural immersion, and collaboration between translators and technology developers.